High School Track Choice and Liquidity Constraints: Evidence from Urban Mexico - Ciro Avitabile; Matteo Bobba; Marco Pariguana (Institute of Labor Economics (IZA), 2017)
We study how a large household windfall affects sorting of relatively disadvantaged youth over high school tracks by exploiting the discontinuity in the assignment of a welfare program in Mexico. The in-cash transfer is found to significantly increase the probability of selecting vocational schools as the most preferred options vis-a-vis other more academically oriented education modalities. We find support for the hypothesis that the transfer relaxes the liquidity constraints preventing relatively poor students from choosing a schooling career with higher out-of-pocket expenditures and higher expected returns. The observed change in stated preferences across tracks effectively alters school placement, and bears a positive effect on on-time graduation.
Keywords: I21; I24; J24; 330; school choice; tracking; financial constraints; vocational education; returns to education; regression discontinuity design